2009
DOI: 10.1088/0004-637x/695/1/l10
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Burst Light Curves in the Relativistic Turbulence and Relativistic Subjet Models

Abstract: Randomly oriented relativistic emitters in a relativistically expanding shell provides an alternative to internal shocks as a mechanism for producing GRBs' variable light curves with efficient conversion of energy to radiation. In this model the relativistic outflow is broken into small emitters moving relativistically in the outflow's rest frame. Variability arises because an observer sees an emitter only when its velocity points towards him so that only a small fraction of the emitters are seen by a given ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
113
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 20 publications
3
113
1
Order By: Relevance
“…Since magnetic reconnection can be the source of turbulence (e.g. Lazarian et al 2015), the emitting eddies have turbulent motions within the comoving frame of the outflow, as prescribed in the relativistic turbulence model (Lazar et al 2009;), At variance with the previous models, fast variability originates in the emission region (Lyutikov & Blandford 2003;Lyutikov 2006). The relative strength of the fast over the slow component reflects the filling factor of the eddies in the jet.…”
Section: Discussionmentioning
confidence: 96%
“…Since magnetic reconnection can be the source of turbulence (e.g. Lazarian et al 2015), the emitting eddies have turbulent motions within the comoving frame of the outflow, as prescribed in the relativistic turbulence model (Lazar et al 2009;), At variance with the previous models, fast variability originates in the emission region (Lyutikov & Blandford 2003;Lyutikov 2006). The relative strength of the fast over the slow component reflects the filling factor of the eddies in the jet.…”
Section: Discussionmentioning
confidence: 96%
“…It is a candidate for explaining (i) particle acceleration at pulsar wind termination shocks (Kirk & Skjaeraasen 2003;Pétri & Lyubarsky 2007;Sironi & Spitkovsky 2011a); (ii) the flat radio spectra from galactic nuclei and AGNs (Birk et al 2001) and from extragalactic jets (Romanova & Lovelace 1992); (iii) GeV flares from the Crab nebula (Bednarek & Idec 2011;Uzdensky et al 2011;Cerutti et al 2012aCerutti et al ,b, 2013; (iv) flares in active galactic nuclei (AGN) jets (Giannios et al 2009) or in gamma-ray bursts (Lyutikov 2006a;Lazar et al 2009); (v) the heating of AGN and microquasar coronae and the observed flares (Di Matteo 1998;Merloni & Fabian 2001;Goodman & Uzdensky 2008;Reis & Miller 2013;Romero et al 2014;Zdziarski et al 2014); (vi) the heating of the lobes of giant radio galaxies (Kronberg et al 2004); (vii) transient outflow production in microquasars and quasars (de Gouveia dal Pino & Lazarian 2005;de Gouveia Dal Pino et al 2010;Kowal et al 2011;Dexter et al 2014); (viii) gamma-ray burst outflows and non-thermal emissions (Drenkhahn & Spruit 2002;Giannios & Spruit 2007;McKinney & Uzdensky 2012); (ix) X-ray flashes (Drenkhahn & Spruit 2002); or (x) soft gamma-ray repeaters (Lyutikov 2006b;Uzdensky 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This turbulent process, plus the inverse Compton mechanism, was applied to the study of radiation in GRB 080319B ). In the turbulent fluid, the random and small emitters can produce short-time variabilities, indicating many pulses shown in the GRB prompt light curve (Lyutikov 2006;Lazar et al 2009). It is worth noting the key point of this "jetin-jet" model: these microemitters within the bulk jet of GRB explosion also have a jet structure.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the multiwavelength spectral result of GRB 100728A is especially precious to constrain our theoretical model of jitter/JSC radiation. Furthermore, from the clues of Lyutikov (2006) and Lazar et al (2009), we expect that the observed gross emission from a bulk jet launched by GRB explosion might be related to the emissions from the small-scale emitters with the minijet structure. Therefore, in this paper, we stress the following issues.…”
Section: Introductionmentioning
confidence: 99%